Structural basis for a two-dimensional flexible pharmaceutical solvate crystal: indomethacin methanol - Bhowmik, Aritra; Bamane, Sanjivani; Mishra, Manish Kumar (CrystEngComm, 2024)
We report the first two-dimensionally (2D) elastically bendable and twistable pharmaceutical-solvate crystal, indomethacin methanol. Its flexibility is due to interlocked packing and a structural buffer acting like isotropic interactions. For the first time, we utilized Raman spectroscopy on the two elastic faces of a bent crystal region, revealing the inhomogeneous molecular distribution in the crystal structure during bending and validating the mechanistic model of the 2D elastic crystal. We present the first 2D elastic pharmaceutical-solvate crystal and utilized Raman spectroscopy to reveal inhomogeneous lattice distribution during bending.

Caffeine vs. theophylline cocrystals: insights into structure-mechanical behavior and piezoelectricity - Bhowmik, Aritra; Bamane, Sanjivani; Saxena, Ashish Kumar; Mishra, Manish Kumar (Crystal Growth & Design, 2025)
Cocrystallization offers a versatile approach to modulate the physicochemical including mechanical properties of active pharmaceutical ingredients (APIs). In this study, we employ crystal engineering principles to design cocrystals of two structurally similar methylxanthine compounds-caffeine (CAF) and theophylline (THP)-with 3,5-dinitrosalicylic acid (DNSA) and 3,5-dinitrobenzoic acid (DNBA) as coformers. The resulting cocrystals and cocrystal polymorphs displayed diverse architectures-2D layers, corrugated sheets, and 3D interlocked structures-showing distinct deformation characteristics. Particular attention was given to the mechanical shearing of the layered structure cocrystals THP-DNBA and CAF-DNBA-I, which are critical for pharmaceutical manufacturing processes such as tablet compaction. The sheared fragmented crystal of THP-DNBA also shows plastic bending deformation. On the other hand, the CAF-DNSA, CAF-DNBA-II, and THP-DNSA cocrystals are brittle due to the absence of a flat layer structure. Our findings reveal that structural features such as flat molecular geometry, pi-stacking, and weak interlayer interactions play crucial roles in promoting plastic deformation via shearing and plastic bending. Nanoindentation studies have been performed on the major faces of all the cocrystals to quantify their mechanical properties. Notably, the CAF-DNBA-I cocrystal also exhibited piezoelectric properties. This work provides valuable insights into the structure-mechanical property relationship in pharmaceutical cocrystals and underscores the potential of cocrystallization in addressing formulation-related challenges.